ChemInform Abstract: Catalytic Conjugate Addition of Acyl Anion Equivalents Promoted by Fluorodesilylation. Issue 22 (3rd June 2014) - Denmark, Scott E.; Cullen, Lindsey R.
Abstract Conjugate addition of acyl anion equivalents derived from 2‐silyl‐1, 3‐dithianes to α, β‐unsaturated ketones and esters is achieved using readily available Bu4NF as catalyst.